Effects of Apilarnil on Semen Parameters During Ram Semen Short-Term Storage - Acisu, Tutku Can; Koca, Recep Hakkı; Akarsu, Serkan Ali; Çakir Cihangiroğlu, Aslıhan; Badilli, Nida; Arkali, Gözde; Gür, Seyfettin (Ataturk Universitesi, 2025)
This study aimed to investigate the effects of different concentrations of apilarnil (APL) added to semen diluent on the short-term storage of ram semen. For this purpose, six Akkaraman rams aged 1.5 years were used in the study outside the breeding season. Semen was collected from the rams twice a week with the help of an artificial vagina. Semen was first analyzed and ejaculates with a total motility score of 70% and above were pooled. The pooled ejaculates were divided into 5 equal parts and reconstituted with tris-egg yolk diluent containing 0%, 0.5%, 1%, 1%.5% and 2% APL. Diluted semen samples were stored at 4oC for 72 hours. As a result of the analyses, no statistically significant difference was observed between the groups in terms of total motility at 0 hour, while progressive motility was significantly higher in the 0.5% APL group (P < .005). While rapid spermatozoa rate, curvilinear velocity (VCL), and linear velocity (VSL) were high in the control group in all time periods, medium, and slow spermatozoa rates were high in 1% and 1.5% APL groups (P < .05). At 0 and 72 hours, the control group had the highest malondialdehyde (MDA) level (P < .001). Glutathione (GSH) level and glutathione peroxidase (GSH-Px) and catalase (CAT) activities were significantly lower in the control group at 0 and 72 hours. In conclusion, 0.5-1.5% APL added to semen diluent for short-term storage of ram semen has a positive effect on semen quality and oxidant status. © 2025, Ataturk Universitesi. All rights reserved.
Koç Spermasının Kısa Süreli Saklanması Sırasında Apilarnil'in Sperma Parametreleri Üzerindeki Etkileri
Keywords: Apilarnil; CASA; cooling; ram; sperm